A fast calculation method of rolling times in the GNSS real-time compaction quality supervisory system. (February 2019) - Huang, Shengxiang; Zhang, Wen
Highlights: A calculation method of rolling times in the GNSS real-time compaction quality supervisory system is proposed. The method can work out the rolling times of every pixel in the image by using the Alpha blending algorithm in computer graphics. The method is simple and fast, and the graph of rolling figure can be fine at pixel level, achieving the real-time and accurate evaluation of rolling times. Abstract: The GNSS (Global Navigation Satellite System) real-time compaction quality supervisory system realizes the on-site quality control and process control for the construction quality of the roller compaction for filling engineering. According to the need of the GNSS real-time supervisory system in how to calculate the rolling times quickly and accurately, as well as the characteristics of the rolling track in the construction, a new method is put forward as follows: keeping the real rolling track width information, superimposing the transparent band plotted at scale and calculating the rolling times of every pixel in the image by using the alpha blending algorithm in computer graphics. In this paper, the fast calculation method of rolling times based on alpha blending algorithm will be introduced in detail. Comparing with the conventional method of grid, experiment and application results show that the new method is simple, fast and precise, that the graph of rolling figure can be fine at pixel level, making the calculation of rolling times real-time and accurate.